Strengthening the Role of Experts in Supporting the Effectiveness of Functions in the Regional House of Representatives - Muhtar, Muhtar; Nur, Rismawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
The Regional House of Representatives (DPRD) plays a strategic role in safeguarding local democracy through the implementation of legislative, budgeting and supervisory functions. However, reality shows that the effectiveness of the implementation of official functions is often constrained by the limited technical and substantive capacity of council members. In this context, the existence of experts becomes a vital instrument as a provider of scientific and technocratic support. This study aims to analyze the strategic role of DPRD experts in supporting the implementation of official functions and formulate strategies to optimize their utilization. Using a juridical-normative approach, the results show that the existence of experts has not been institutionalized optimally due to three main problems, namely a recruitment system that is not based on meritocracy, a lack of professional capacity building schemes, and a weak institutional framework that systematically regulates their duties and functions. In an effort to strengthen the role of DPRD experts, the reformulation of recruitment policies, the preparation of competency standards, and the establishment of expert management units under the DPRD Secretariat are key strategies to ensure the professionalism and substantive contribution of experts to the implementation of official functions. With adequate regulative and institutional strengthening, experts can act as a strategic partner to improve the quality of legislation and accountability of local government.